The Impact of Lean Management Concept on The Development and Financial Security of Polish Enterprises - Monika SZCZERBAK (Communications of International Proceedings, 2022)
The success or failure of a company is to a large extent dependent on its management, that is either utilizing or wasting possibilities to adjust the company to the rapidly evolving requirements of the environment, which is equivalent to changing stereotypes and old management habits. The aim of the article is to present the concept of lean management as a condition for ensuring financial stability, efficiency and performance of a modern organization. The importance of selected lean management methods and techniques focused on quality improvement, development, elimination of areas generating too high costs, effective resource management and strengthening competitiveness as well as the interest of Polish enterprises in lean management tools based on own research is presented.
Keywords: Lean Management; Lean Accounting; Kaizen; Tools to Improve Management; Financial Security